OPTIMALISASI PENERAPAN SUMUR RESAPAN UNTUK MENURUNKAN DEBIT BANJIR - Kurniani, Dwi; Suripin, Suripin (MEDIA KOMUNIKASI TEKNIK SIPIL, 2007)
The increasing demand for water supply has incresed groundwater pumping. On the other hand, the fast growing development has altered the pervious land surface of recharge area to impervious surface that reduces natural recharge. The groundwater is therefore inbalance the discharge greater than the recharge. As conssequence there is groundwater defisit, and the groundwater piezometric pressure goes down. The further impact of the lowering ground water is landsubsidence. The awareness towards the use of artificial recharge to augment ground water supplies have to be activated. Artificial recharge by using recharge wells is one of the possible measures to replenish an aquifer. The technology of recharge wells is generally well understood by both the technicians and the general population, and no special tools are needed to dig drainage wells. This research is aimed to determine and formulate the capacity of the recharge wells, both shallow and deep wells, by setting up a psysical model. The result indicated that depression curve of water table and/or piezometric pressure was logaritmic function both for shallow and deep wells. The capacity of the depends on the head, permeability, the aquifer thickness, and type of well. The capacity of the wall recharge well is higher than the last. The obtained formula gives the higher capacity value than that of dupuit. It may happen due to the deviation of the soil permeability between the measured and the actual in the test preparation